Seat Belt and Child Seat Use in Lipetskaya Oblast, Russia: Frequencies, Attitudes, and Perceptions - Ma, Sai; Tran, Nhan; Klyavin, Vladimir E.; Zambon, Francesco; Hatcher, Kristin W.; Hyder, Adnan A. (Traffic injury prevention, 2012)
Objective: Despite the importance of understanding seat belt use patterns among drivers and passengers for the purpose of direct interventions or monitoring improvements, no study has described wearing rates for all seat positions in Russia. This study describes observed seat belt use and knowledge, attitudes, and perceptions of seat belt use in Lipetskaya Oblast, Russia. Methods: An observational study on the use of seat belts and child restraints in the Lipetskaya region conducted during October 2010 collected data in 6 districts and on 3 different road types. A roadside survey gathered information on knowledge, attitudes, and perceptions toward the use of seat belts from randomly selected drivers. Frequencies of seat belt use by seat position, gender, and road type were calculated. A multivariable logit model disclosed the associations between seat belt use and sociodemographic factors. The study design permitted comparison of observed seat belt use to self-reported seat belt use. Results: A total of 25,795 vehicles and 39,833 drivers and passengers contributed observations. Overall, 55 percent of drivers were observed to be using seat belts. More than half (58%) of front seat passengers wore seat belts and only 9 percent of back seat passengers were observed to be wearing seat belts; 11 percent of cars with children had any type of child safety measure. Drivers on urban roads were less likely to wear seat belts compared to those on main highways and rural roads. Nearly 60 percent of survey respondents mentioned "seat belts save lives," and more than half mentioned law requirements and fines. Conclusions: Although the observed seat belt use in Lipetskaya Oblast is much higher than previous estimates in Russia, overall wearing rates remain far from universal. Rear seat passengers and children are particularly at risk. Because combined education and enforcement has proven to be effective elsewhere, such interventions are needed to improve seat belt use.